Deciphering the urinary microbiome and urological cancers: from correlation to mechanisms and treatment - Zheng, Zunwen; Xie, Deqian; Han, Yongzheng; Li, Guandu; Wang, Shijin; Zhang, Xiaoman; Huang, Tao; Xu, Wenfei; Wu, Guangzhen (Frontiers in Microbiology, 2025)
Given that the sterility of urine and the urinary tract has been questioned by research, urinary microbiome dysbiosis has been recognized as one of the potential cancer-promoting factors. The composition of the urinary microbial community in healthy individuals has a relatively high similarity at the phylum level, with factors like age and gender influencing the expression and distribution. In contrast, the urinary microbiome of patients with urologic cancers shows significant variability and diversity depending on the type of cancer. Most of the early studies focused on the distribution, aggregation, and expression of microbiota in urologic cancers, warranting advanced studies on the causal relationship between microbes and urologic cancers. Bladder and prostate cancer tumorigenesis and progression can be influenced by microbes through chronic inflammatory or immunomodulatory pathways making them cancer models strongly associated with the urinary microbiome. Here, we summarize the expression characteristics of the microbiomes associated with these cancers and analyze the pathophysiological mechanisms and signaling pathways of the microbiome in the tumor promotion or suppression. By examining the role played by the urinary microbiome in the pathogenesis of urologic cancers, we assess the potential of specific microbial groups as biomarkers for diagnosis and surveillance. Additionally, involving the microbiome or using adjunctive participation in tumor therapy is becoming an emerging cancer treatment option. Improving urinary microbial homeostasis in urinary cancers by direct treatment with microbial products, microbial co-immunotherapy, probiotic-assisted therapy, and fecal microbial transplantation may broaden the scope of therapy and enhance the efficacy of conventional medicines.